Scenario analysis and the economic and financial risks from climate change - Erik Ens; Craig Johnston (Bank of Canada, 2020)
Central banks are increasingly focused on the risks from climate change for the economy and financial system. Two sets of risks are of particular concern: physical risks from more frequent and severe weather events, and transition risks from the move toward a lower-carbon intensive economy. This paper adapts climate-economy models that have been applied in other contexts for use in climate-related scenario analysis. We consider illustrative scenarios for the global economy that could generate economic and financial system risks by varying assumptions on key variables such as climate policy in plausible ways. The results show significant economic implications from climate change and the transition to a low-carbon economy. The timing and magnitude of global GDP and sectoral impacts, among other outcomes, vary considerably under the mix of scenarios. These risks touch on the interests of a broad range of stakeholders across the private and public sectors. In addition to central banks and governments, these risks could affect financial institutions, resource-intensive industries and other private sector firms. Further improvements in scenario analysis, as well as wider-spread use across the public and private sectors, could lead to a better understanding of the risks and opportunities of climate change.
Keywords: C68; D58; E50; O44; P18; Q4; Q54; Q55; 330; Climate change; Economic models; Financial stability; International topics